Preterm delivery in Ghana: challenges and implications for maternal mental health trajectories - David Kwame Kumador; Alberta Opoku-Mensah; Vivian Tackie-Ofosu; Sheriffa Mahama; Justice Owusu-Bempah; Crossby Osei Tutu (PLoS ONE, 2025)
Purpose The present study examined mothers’ experiences with preterm infants in Accra, Ghana, at a time when the COVID-19 pandemic, existing poverty, and global economic depressions severely challenged access to communal, familial, and individual resources. We argue that, in a family crisis, contextual and external institutional resources, such as access to quality healthcare resources, play crucial roles in mothers’ risk exposure and adaptation. Study design/methodology/approach Using a qualitative approach with an immersive exploratory-descriptive design, the study interviewed twenty-five (25) mothers whose preterm infants were discharged from the Neonatal Intensive Care Unit (NICU) of Korle Bu Teaching Hospital in Accra, Ghana. Findings The study showed that mothers of preterm infants experienced varying range of challenges, including diminished appetite, decreased productivity, and feelings of hopelessness, both during and following their infants’ hospitalization. Having access to adequate income, information, medication, and experienced medical practitioners remains critical to the management of stressful situations associated with the care of preterm children. Conclusion for practice Access to funding, preterm information, quality medication, and qualified health professionals can help mothers of preterm infants’ better deal with negative experiences than those who do not have adequate amounts of these resources. Access to critical resources can safeguard mothers’ mental health and the survival of preterm infants within the first year of delivery. A policy on the existing national health insurance scheme can be enacted to expand coverage and absorb the cost of care for the mother and child within the first eighteen months after delivery.